Multiple Group Membership and Well-Being: Is There Always Strength in Numbers? - Sønderlund, Anders L.; Morton, Thomas A.; Ryan, Michelle K. (Frontiers in Psychology, 2017)
A growing body of research points to the value of multiple group memberships for individual well-being. However, much of this work considers group memberships very broadly and in terms of number alone. We conducted two correlational studies exploring how the relationship between multiple group membership and well-being is shaped by (a) the complexity of those groups within the overall self-concept (i.e., social identity complexity: SIC), and (b) the perceived value and visibility of individual group memberships to others (i.e., stigma). Study 1 (N = 112) found a positive relationship between multiple group membership and well-being, but only for individuals high in SIC. This effect was mediated by the perceived ease of perceived identity expression and access to social support. Study 2 (N = 104) also found that multiple group memberships indirectly contributed to well-being via perceived identity expression and social support, as well as identity compatibility and perceived social inclusion. But, in this study the relationship between multiple group memberships and well-being outcomes was moderated by the perceived value and visibility of group memberships to others. Specifically, possessing multiple, devalued and visible group memberships compromised well-being relative to multiple valued group memberships, or devalued group memberships that were invisible. Together, these studies suggest that the benefits of multiple group membership depend on factors beyond their number. Instead, the features of group memberships, individually and in combination, and the way in which these guide self-expression and social action, determine whether these are a benefit or burden for individual well-being.